2020
DOI: 10.1080/02607476.2020.1733400
|View full text |Cite
|
Sign up to set email alerts
|

Service-learning in physical education teacher education: towards a critical and inclusive perspective

Abstract: The purpose of this study was to analyse the impact of servicelearning (SL) in physical education teacher education students (PETEs). The PETEs (n = 169) completed one of the editions of a SL program carried out between 2015-2018. This program consisted of designing and leading motor game sessions to facilitate the inclusion of 116 children with special educational needs (SEN). The program was based on Kolb's learning stages to promote reflection and critical thinking. Reflective journals were used as an instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
22

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 43 publications
2
28
0
22
Order By: Relevance
“…Chiva-Bartoll et al [ 41 ] studied children with special educational needs and obtained an inclusive, critical educational experience that allowed them to link theory and practice in a particularly effective way. In turn, Ruiz et al [ 54 ] reported findings related to academic and professional learning when working with older adults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiva-Bartoll et al [ 41 ] studied children with special educational needs and obtained an inclusive, critical educational experience that allowed them to link theory and practice in a particularly effective way. In turn, Ruiz et al [ 54 ] reported findings related to academic and professional learning when working with older adults.…”
Section: Resultsmentioning
confidence: 99%
“…Chiva-Bartoll et al [ 41 , 42 ] studied values, personal attitudes, and/or personal life plans, concluding that SL promotes subjective happiness and pro-social attitudes [ 42 ]. Ruiz et al [ 54 ] analyzed social sensitivity and disconfirmation of negative stereotypes, satisfaction and personal growth, and desire for social justice, resulting in relevant items for PETE students.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have offered a panoramic overview of SL impact in terms of academic, professional, and social effects [22,23]. These results are also endorsed by many studies in the field of physical activity and sports sciences [15,16,24,25]. Therefore, SL may be useful for enabling students to understand and learn about aging and older adults.…”
Section: Introductionmentioning
confidence: 83%
“…By focusing on this particular aspect of the research, which aligns with the higher education challenge of updating its pedagogical paradigm towards a more effective training, we hypothesize that SL could improve the PETE students’ EP. Particularly, this is supported by current literature that suggests students’ improvements in self-concept and self-esteem can be made through personal reflection about oneself, which in turn encourages students to adjust their behaviour within the class group, thus increasing their social competences and communication skills [ 20 ]. Likewise, the inherent SL reflection processes would allow students to increase their motivation towards the task and professional-related skills [ 8 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 68%
“…Initially, Billig [ 15 ] and Eyler and Giles [ 16 ] classified the results of the SL effects into four categories: academic outcomes, personal outcomes, social outcomes, and citizenship values. More recently, Furco [ 17 ] grouped the SL outcomes into six different categories, drawing upon several research evidence from recent contributions: (1) students’ academic and cognitive development [ 7 , 8 , 18 ], (2) students’ civic engagement [ 7 , 19 , 20 ], (3) students’ vocational and professional development [ 21 ], (4) students’ ethical and moral growth [ 22 ], (5) students’ personal and identity growth [ 23 ], and (6) students’ social development [ 24 , 25 ]. Therefore, one can sensibly hypothesise that SL can contribute to the development of Effective Personality (EP).…”
Section: Introductionmentioning
confidence: 99%